2010
DOI: 10.4161/cbt.9.10.11552
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin upregulates death receptor 5 expression and cooperates with TRAIL to induce apoptosis in human prostate cancer cells

Abstract: Dihydroartemisinin (DHA) is a derivative of artemisinin and is an effective anti-malaria therapeutic used worldwide. In this paper, we report that DHA is as a potential anticancer drug for prostate cancer. Our data indicate that DHA suppresses the PI3-K/Akt and ERK cell survival pathways and triggers the induction of death receptor DR5 and activation of extrinsic and intrinsic cell death signaling. DHA-mediated DR5 induction appears to occur via increased transcriptional activity of DR5 promoter. Our data also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 29 publications
(36 reference statements)
3
41
0
Order By: Relevance
“…Additionally, DHA exerts an antineoplastic effect in prostate cancer cells by increasing death receptor 5 expression (24) and induces NOXA-dependent mitochondrial cell apoptosis in melanoma cells with upregulation of cellular oxidative stress (25), furthermore, DHA triggers cell cycle arrest via effects on the AKT/GSK3β/cyclin D1 pathway in A549 lung cancer cells (26). DHA could also inhibit the Wnt/β-catenin signaling pathway in lung cancer, and the expressions of key proteins including Wnt5-a/b, LRP6 and Dvl2 in the Wnt/β-catenin signaling pathway were significantly decreased (27).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DHA exerts an antineoplastic effect in prostate cancer cells by increasing death receptor 5 expression (24) and induces NOXA-dependent mitochondrial cell apoptosis in melanoma cells with upregulation of cellular oxidative stress (25), furthermore, DHA triggers cell cycle arrest via effects on the AKT/GSK3β/cyclin D1 pathway in A549 lung cancer cells (26). DHA could also inhibit the Wnt/β-catenin signaling pathway in lung cancer, and the expressions of key proteins including Wnt5-a/b, LRP6 and Dvl2 in the Wnt/β-catenin signaling pathway were significantly decreased (27).…”
Section: Discussionmentioning
confidence: 99%
“…Artemisinin and its derivatives such as Dihydroartemisinin (DHA) have been reported to induce apoptosis in pancreas, prostate, colon and neuroblastoma [8][9][10][11]. Dihydroartemisinin has been found as an antiproliferative agent in vitro and in vivo [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroartemisinin has been found as an antiproliferative agent in vitro and in vivo [25]. In particular, Dihydroartemisinin was considered as a potential antitumor agent in several cancer cell lines [6][7][8][9][10][11][12]. Based on these findings, we explored to determine the growth inhibitory effect of Dihydroartemisinin on the human skin cancer cells and the possible mechanism of its action was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHA has been approved for the treatment of multidrug-resistant malaria and has an excellent safety profile [15,16]. Some laboratory studies have suggested that artemisinin derivatives, including DHA, also have significant effects against various human tumors, such as leukemia cells [17], prostate cancer [18], ovarian cells [19], pancreatic cancer [20], lung adenocarcinoma, and non-small cell lung cancer [21,22]. A previous study demonstrated that DHA could effectively inhibit U87 glioma cell proliferation, invasion, and angiogenesis [23].…”
Section: Introductionmentioning
confidence: 99%